Lung Microbiome Analysis in Steroid-Naїve Asthma Patients by Using Whole Sputum - Jung, Jae-Woo; Choi, Jae-Chol; Shin, Jong-Wook; Kim, Jae-Yeol; Park, In-Won; Choi, Byoung Whui; Park, Heung-Woo; Cho, Sang-Heon; Kim, Kijeong; Kang, Hye-Ryun (Tuberculosis and respiratory diseases, 2016)
Although recent metagenomic approaches have characterized the distinguished microbial compositions in airways of asthmatics, these results did not reach a consensus due to the small sample size, non-standardization of specimens and medication status. We conducted a metagenomics approach by using terminal restriction fragment length polymorphism (T-RFLP) analysis of the induced whole sputum representing both the cellular and fluid phases in a relative large number of steroid naïve asthmatics. Induced whole sputum samples obtained from 36 healthy subjects and 89 steroid-naїve asthma patients were analyzed through T-RFLP analysis. In contrast to previous reports about microbiota in the asthmatic airways, the diversity of microbial composition was not significantly different between the controls and asthma patients (p=0.937). In an analysis of similarities, the global R-value showed a statistically significant difference but a very low separation (0.148, p=0.002). The dissimilarity in the bacterial communities between groups was 28.74%, and operational taxonomic units (OTUs) contributing to this difference were as follows: OTU 789 (Lachnospiraceae), 517 (Comamonadaceae, Acetobacteraceae , and Chloroplast), 633 (Prevotella), 645 (Actinobacteria and Propionibacterium acnes), 607 (Lactobacillus buchneri, Lactobacillus otakiensis, Lactobacillus sunkii, and Rhodobacteraceae), and 661 (Acinetobacter, Pseudomonas, and Leptotrichiaceae), and they were significantly more prevalent in the sputum of asthma patients than in the sputum of the controls. Before starting anti-asthmatic treatment, the microbiota in the whole sputum of patients with asthma showed a marginal difference from the microbiota in the whole sputum of the controls.